Hybrid Convergence Life-Cycle Model For Large Scale Projects - Balakrishnan, Vasuthevan; Lee, Sai Peck (Malaysian Journal of Computer Science, 1999)
Much has been said about the problems that software engineers face in developing large systems. Traditionally, developers have adopted structured analysis and design methodology in developing systems that has been working fairly efficiently until now. Much complaint has been thrown at this methodology. As with this methodology, most complex software systems raise numerous software engineering problems such as design, development, requirements compliance, evolution and maintenance. To these problems, Object-Oriented (OO) methods and tools claim to bring a solution. The trend now is to use OO technology. But is this new approach mature enough for developing large and industrial strength applications? This paper presents an overview of the two methodologies, assesses its strength and weaknesses and suggests a new model for efficient development of large-scale systems incorporating both the strengths of structured and objectoriented methodologies.